Théâtre(s) sous un crâne - Maria de Jesus Cabral (Carnets)
The stepping stone of this paper is the explanation of the concept of mental theatre, core to Stéphane Mallarmé’s thought and work, in order to assess the links it establishes with the theatrical ex-centrism within Fernando Pessoa, namely in his process of heteronym creation. This shall be equated based on the psycho-pathological element and through the concepts of manner and madness (Dessons, 2004, 2010). The The third part of this paper deals with a comparative approach to Igitur or la Folie d’Elbehnon and Faust, tragédie subjective, both left unfinished and both part of an eclectic gender against any form of positivity.